2013
DOI: 10.1002/eji.201343630
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lived Plasmodium falciparum specific memory B cells in naturally exposed Swedish travelers

Abstract: Antibodies (Abs) are critical for immunity to malaria. However, Plasmodium falciparum specific Abs decline rapidly in absence of reinfection, suggesting impaired immunological memory. This study determines whether residents of Sweden that were treated for malaria following international travel maintained long‐lasting malaria‐specific Abs and memory B cells (MBCs). We compared levels of malaria‐specific Abs and MBCs between 47 travelers who had been admitted with malaria at the Karolinska University Hospital be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 61 publications
6
45
0
Order By: Relevance
“…This suggests that robust immunological memory can result even when antigen exposure is infrequent (as is the case for VAR2CSA). This conclusion is supported by data on acquisition of immunity in settings with a low level of endemicity, in travelers, and in experimentally infected mice (17,59,71). The finding that FV2-specific memory B-cell frequencies did not depend on time since last pregnancy (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This suggests that robust immunological memory can result even when antigen exposure is infrequent (as is the case for VAR2CSA). This conclusion is supported by data on acquisition of immunity in settings with a low level of endemicity, in travelers, and in experimentally infected mice (17,59,71). The finding that FV2-specific memory B-cell frequencies did not depend on time since last pregnancy (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…It has been suggested that this could explain the paradoxical inverse relationship between parasite exposure and acquired immunity observed in some studies (58,59). However, the antigen specificity of phenotypically identified "atypical"/"exhausted" memory B cells observed in these papers was not estab- lished, and other recent studies did not find evidence that B-cell memory for P. falciparum antigens is deficient (16,17) or that "atypical" P. falciparum-specific B cells are dysfunctional (18). Careful studies of the phenotype-function relationships among B-cell subsets with known antigen specificity are clearly warranted.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, several studies have demonstrated stable antibody responses to PfMSP1-19, P. falciparum merozoite surface protein 2 (PfMSP2), and PfAMA1 antigens (31,33,34). Moreover, longlived antibody and memory B-cell responses to P. falciparum (PfMSP1-19, PfMSP2, PfCSP, and PvAMA1) and P. vivax (PvMSP1-19, PvAMA1, and PvDBP) were identified recently (35,36). Here, we also observed that antibodies against several PvTRAgs (TRAg_13, TRAg_15, and TRAg_29) and PvMSP1-19 were detected in individuals from Jiangsu Province, China (where malaria is not recently endemic), who had had a vivax malaria episode 5 or 12 years before.…”
Section: Discussionmentioning
confidence: 99%